2016
DOI: 10.1167/tvst.5.5.5
|View full text |Cite
|
Sign up to set email alerts
|

Bioptic Telescope Use and Driving Patterns of Drivers with Age-Related Macular Degeneration

Abstract: PurposeTo investigate the telescope use and driving patterns of bioptic drivers with age-related macular degeneration (AMD).MethodsA questionnaire addressing telescope use and driving patterns was administered by telephone interview to three groups of bioptic drivers: AMD (n = 31; median 76 years); non-AMD first licensed with a bioptic (n = 38; 53 years); and non-AMD first licensed without a bioptic (n = 47; 37 years). Driving patterns of bioptic AMD drivers were also compared with those of normal vision (NV) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
2

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…16 In general, participants spent only 1.6% of total driving time using their bioptic telescope, which is lower than the median estimate of 5% based on bioptic drivers' self-reports in a previous questionnaire study. 20 However, we found that two drivers spent a much higher percentage of driving time (46.1% and 17.8%) using their bioptic telescope. One of these drivers used the telescope briefly but very frequently whereas the other used the telescope less frequently but many bioptic uses were long (median 4.0 seconds).…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…16 In general, participants spent only 1.6% of total driving time using their bioptic telescope, which is lower than the median estimate of 5% based on bioptic drivers' self-reports in a previous questionnaire study. 20 However, we found that two drivers spent a much higher percentage of driving time (46.1% and 17.8%) using their bioptic telescope. One of these drivers used the telescope briefly but very frequently whereas the other used the telescope less frequently but many bioptic uses were long (median 4.0 seconds).…”
Section: Discussionmentioning
confidence: 58%
“…Bowers et al investigated bioptic telescope use patterns and driving patterns by telephone interview. 19,20 Owsley et al 21 administered a questionnaire to examine whether the telescope was helpful in on-road situations. One limitation of these studies is that self-reports might not always be reliable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 This kind of glance occupies less than 1.5% of the whole driving time. 8,9 In general, there are different kinds of bioptic telescopes, such as monocular and binocular telescopes, Keplerian and Galilean telescopes. 10 Different states have different requirements on the bioptic for driving.…”
Section: Introductionmentioning
confidence: 99%
“…These drivers’ low level of visual acuity sets them apart from the drivers with conventional levels of visual acuity. Bioptic drivers use the telescope mainly for navigation and reading the signs 22,23 , which means that they use their bioptic telescope for only a small proportion of total driving time, adhering to the bioptic driving guidelines which addresses concern that use of the bioptic telescope may block the field of view 24 . Luo and Peli 12 recorded the actual driving of two bioptic drivers and found that their bioptic use was as low as 1%, meaning that for 99% of the time these drivers drove with their low visual acuity.…”
Section: Introductionmentioning
confidence: 99%